2003
DOI: 10.1159/000072705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Angiotensin II Receptor Antagonist and Angiotensin-Converting Enzyme Inhibitors on Burst Forming Units-Erythroid in Chronic Hemodialysis Patients

Abstract: Background: Angiotensin-converting enzyme (ACE) inhibitors have been reported to reduce the response to erythropoietin (EPO) administration in chronic hemodialysis patients, but the mechanism for this effect has not yet been clarified. To clarify the mechanism of ACE inhibitors- and angiotensin II type 1 (AT1) receptor antagonist-induced anemia in hemodialysis patients, we examined the effect of ACE inhibitors and AT1 receptor antagonist on burst-forming units-erythroid (BFU-E) in the peripheral blood of hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
3
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
0
28
3
2
Order By: Relevance
“…Repetitive BFU-E expansion and/or peripheral recruitment during decompensations may later contribute to their quantitative exhaustion in the compensated state. While ACE-inhibitors, ARBs and β 2 -adrenergic receptor blockers could also account for low BFU-E counts in our anaemic subjects [40,41], the use of these drugs did not differ between anaemic and non-anaemic patients, suggesting that other factors intrinsic to the deranged milieu of CHF were more likely responsible.…”
Section: Erythropoiesis In Compensated Vs Decompensated Patientsmentioning
confidence: 62%
“…Repetitive BFU-E expansion and/or peripheral recruitment during decompensations may later contribute to their quantitative exhaustion in the compensated state. While ACE-inhibitors, ARBs and β 2 -adrenergic receptor blockers could also account for low BFU-E counts in our anaemic subjects [40,41], the use of these drugs did not differ between anaemic and non-anaemic patients, suggesting that other factors intrinsic to the deranged milieu of CHF were more likely responsible.…”
Section: Erythropoiesis In Compensated Vs Decompensated Patientsmentioning
confidence: 62%
“…Angiotensin converting enzyme inhibitor therapy reduces the response to EPO among dialysis patients 24 and in vitro evidence suggests that the angiotensin II receptor blocker losartan directly suppresses erythroid blast formation. 25 It has been suggested that diuretics which act primarily on the proximal tubule may inhibit EPO production mediated via an increase of local oxygen tension. 26 However, our study did not suggest a relationship between HF medication and serum EPO concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of hypertension (77.5% of our These two groups of antihypertensive agents are particularly recommended in patients with chronic renal insufficiency [11][12][13][14], but the blockade of the renin-angiotensin axis that they produce can worsen anaemia. Several mechanisms have been described in the literature: prevention of the stimulatory effect of angiotensin II on the synthesis of erythropoietin; increase renal plasma flow, reducing the hypoxic stimulus for erythropoietin formation; diminished precursors of erythropoietin; direct effect on red blood stem cells [17]. These drugs are particularly indicated in CKD patients because, with one exception [10], all other studies have been shown them to delay the progression of renal disease [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, both drugs have been shown to worsen anaemia in uraemic patients [15,16]. The pathogenesis of anaemia associated with the blockade of the renin-angiotensin axis is multifactorial [17].…”
Section: Introductionmentioning
confidence: 99%